The Progress and Perspective of Organic Molecules With Switchable Circularly Polarized Luminescence - Gao, Yang; Ren, Can; Lin, Xiaodong; He, Tingchao (Frontiers in Chemistry, 2020)
Circularly polarized luminescence (CPL) has been under intense research for future applications in high-resolution 3D displays, smart sensors, and information technologies. Different types of CPL materials have been developed, but neither the handedness nor the asymmetrical luminescence degree can be inferred from the material composition or the components. CPL materials with switchable handedness or emission wavelength play an important role, reducing the need for repetitive bottom-up synthesis. Here, we have presented switchable CPL behaviors toward multiple reported stimuli, including light irradiation, host–guest interaction, metal ions, pH, solvent, temperature, etc. This summary and discussion of the effective stimuli is aimed to promote rational future material exploration and boost related multidisciplinary applications.